Answer:
P (A ║ B) = 1.98 %
Explanation:
Bayes´ Theorem express
P (A ║ B) = P(A) * P( B ║ A) / P(B)
Now we identify
Event A person infected with a virus. Probability of being infected by a virus is P/A) 0.001
Event B the test was positive. Probability of test positive P(B) = 0,05
Probability of P ( B║ A) is the porbability of test positive given that is infected = 0.99
Then by subtitution in a general equation of the theorem we have
P (A ║ B) = 0.001*0.99/ 0.05
P (A ║ B) = 0.0198 P (A ║ B) = 1.98 %